Two-component organic silicon pouring sealant containing aluminum hydroxide and preparation method of two-component organic silicon pouring sealant
By combining aluminum hydroxide of three particle sizes and double-layer coating modification, along with zinc borate and octaphenyl octsesquioxane, the problems of high viscosity and low flame retardant efficiency of traditional aluminum hydroxide flame retardants in silicone potting compounds were solved, achieving low viscosity and high flame retardant effect.
Patent Information
- Application Number
- CN202511301452.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-12
- Publication Date
- 2025-11-07
AI Technical Summary
Traditional aluminum hydroxide requires a filling amount of over 60 wt% to achieve V-0 flame retardancy, which leads to a sharp increase in viscosity and low flame retardancy efficiency. Furthermore, it has poor compatibility with organosilicon, affecting mechanical properties and thermal stability.
Three different particle sizes of aluminum hydroxide were compounded and modified by double coating with aminosilane and phosphonate. Zinc borate and octaphenyl octasesquioxane were used as flame retardant synergists to form a composite barrier, which reduced the amount of aluminum hydroxide used while maintaining good flame retardant performance and low viscosity.
It significantly improves the flame retardant efficiency and tensile strength of silicone potting compound, while keeping the viscosity below 15000 cP, thus balancing flame retardant and mechanical properties.
Smart Images

Figure CN120904850A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of silicone pouring sealant, and particularly relates to a two-component silicone pouring sealant containing aluminum hydroxide and a preparation method thereof. BACKGROUND
[0002] With the rapid development of modern industrial technology, especially the aerospace, electronic and automobile industries, the performance requirements of various materials continue to improve. Among many materials, high-performance two-component silicone pouring sealant is widely used in electronic packaging, component protection and structural bonding fields due to its excellent electrical insulation, thermal stability and chemical inertness, providing strong material support for the realization of key technologies. This type of material is usually composed of pouring sealant matrix, cross-linking agent, catalyst and various fillers, and can be cured at room temperature or under heating conditions to form a three-dimensional network structure with excellent insulation, waterproofness, heat resistance, weather resistance and certain flame retardant properties.
[0003] Metal hydroxides such as aluminum hydroxide and magnesium hydroxide can decompose to produce water and metal oxide at high temperatures. Water vapor can carry away a large amount of heat, slow down the temperature rise of the material, and at the same time reduce the concentration of combustible and oxygen in the gas phase. Metal oxide can form a protective film on the surface of the matrix, play an insulating and protective role, and prevent further heat transfer, thereby playing a flame-retardant role. However, the flame-retardant effect of metal hydroxides as flame retardants is relatively poor, and a certain amount of addition is required to make the material achieve the ideal flame-retardant state. On the other hand, the large amount of addition of flame retardants will reduce the other properties of the material, such as thermal conductivity, mechanical properties and processing properties.
[0004] Traditional aluminum hydroxide filling amount needs to exceed 60wt% to achieve V-0 grade flame retardation, resulting in a sharp increase in viscosity (>30000mPa.s), low flame retardant efficiency, and the need to sacrifice mechanical properties; at the same time, the surface of aluminum hydroxide is highly polar, has poor compatibility with silicone and is prone to sedimentation, and is prone to dehydration and decomposition under high temperature conditions, reducing thermal stability.
[0005] Therefore, there is an urgent need for a two-component silicone pouring sealant containing aluminum hydroxide, which maintains low viscosity while ensuring good flame retardant properties and mechanical properties of the silicone pouring sealant by selecting aluminum hydroxide with different particle sizes and coating and modifying the aluminum hydroxide, and the combined action of flame-retardant synergists. SUMMARY
[0006] The application aims to provide a hydrogen oxide aluminum containing two-component silicone pouring sealant and a preparation method thereof.
[0007] To achieve the above-mentioned purpose, the application provides the following technical scheme. The application provides a hydrogen oxide aluminum containing two-component silicone pouring sealant in the first aspect, The hydrogen oxide aluminum containing two-component silicone pouring sealant is composed of component A and component B. The component A includes the following components in parts by weight: 35-45 parts of vinyl silicone oil, 50-60 parts of double-layer coated modified hydrogen oxide aluminum, 4-6 parts of flame-retardant synergist, and 0.03-0.09 parts of 1-ethynyl-1-cyclohexanol. The component B includes the following components in parts by weight: 20-30 parts of hydrogen-containing silicone oil and 0.08-0.16 parts of platinum catalyst.
[0008] As a preferred scheme, the vinyl silicone oil can be 35 parts, 37 parts, 39 parts, 41 parts, 43 parts or 45 parts, etc.
[0009] As a preferred scheme, the double-layer coated modified hydrogen oxide aluminum can be 50 parts, 52 parts, 54 parts, 56 parts, 58 parts or 60 parts, etc.
[0010] As a preferred scheme, the flame-retardant synergist can be 4 parts, 4.5 parts, 5 parts, 5.5 parts or 6 parts, etc.
[0011] As a preferred scheme, the 1-ethynyl-1-cyclohexanol can be 0.03 parts, 0.04 parts, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts or 0.09 parts, etc.
[0012] As a preferred scheme, the hydrogen-containing silicone oil can be 20 parts, 22 parts, 24 parts, 26 parts, 28 parts or 30 parts, etc.
[0013] As a preferred scheme, the platinum catalyst can be 0.08 parts, 0.10 parts, 0.12 parts, 0.14 parts or 0.16 parts, etc.
[0014] As a preferred scheme, the preparation method of the double-layer coated modified aluminum hydroxide comprises the following steps: first, coupling treatment of the multi-particle size compounded aluminum hydroxide is carried out by using 3-aminopropyl triethoxysilane to obtain silanized aluminum hydroxide; then, ball milling coating treatment of the silanized aluminum hydroxide is carried out by using organic phosphinic acid salt to obtain double-layer coated modified aluminum hydroxide.
[0015] The present application uses 3-aminopropyl triethoxysilane to couple treat the multi-particle size aluminum hydroxide, and the ethoxyl group of 3-aminopropyl triethoxysilane is hydrolyzed to generate silicon hydroxyl group, then the silicon hydroxyl group reacts with the aluminum hydroxyl group on the surface of the aluminum hydroxide to form Si-O-Al covalent bond by removing water molecules, thereby obtaining silanized aluminum hydroxide; the amino group far away from the surface of the aluminum hydroxide is an organic-friendly active functional group, which can be combined with the organic phosphinic acid salt to realize the coating modification of the organic phosphinic acid salt, thereby obtaining double-layer coated modified aluminum hydroxide.
[0016] As a preferred scheme, the step of coupling treatment comprises the following steps: 80-90 parts of anhydrous ethanol and 10-20 parts of deionized water are uniformly mixed, then 2-4 parts of 3-aminopropyl triethoxysilane is added and stirred uniformly, and then 50-60 parts of multi-particle size compounded aluminum hydroxide is added to react at 70-90 DEG C for 1-2 hours to obtain silanized aluminum hydroxide.
[0017] As a preferred scheme, the step of ball milling coating treatment comprises the following steps: 50-60 parts of silanized aluminum hydroxide and 1-3 parts of organic phosphinic acid salt are added to a planetary ball mill, and ball milling is carried out at a rotating speed of 200-400 rpm for 20-40 minutes to obtain double-layer coated modified aluminum hydroxide.
[0018] The double-layer coated modified aluminum hydroxide of the present application is designed by double-layer coating of amino silane and organic phosphinic acid salt, and under the premise of reducing the addition amount of aluminum hydroxide, the flame retardant efficiency of the organic silicon pouring sealant is significantly improved through phosphorus-silicon-nitrogen synergy (nitrogen element decomposes to generate inert gas to dilute oxygen, phosphorus element generates free radicals to inhibit combustion chain reaction, and silicon element forms silicon skeleton to enhance the thermal stability of carbon layer); at the same time, the amino silane layer of the double-layer coated modified aluminum hydroxide improves the interface bonding between the filler and the matrix, and the organic phosphinic acid salt coating layer reduces the filler agglomeration and reduces the stress concentration, thereby increasing the tensile strength of the organic silicon pouring sealant.
[0019] As a preferred scheme, the organic phosphinic acid salt is zinc phenylphosphinate or iron ethylphenylphosphinate.
[0020] The present application uses organic phosphinic acid salt containing aromatic hydrocarbon, and since the aromatic group has better thermal stability and higher carbon content than linear or branched alkyl group, it can form more complete carbon layer during combustion, and has stronger heat insulation and oxygen insulation capacity, thereby effectively improving the flame retardant performance of the material.
[0021] As a preferred scheme, the multi-particle size compounded aluminum hydroxide comprises small particle size aluminum hydroxide, medium particle size aluminum hydroxide and large particle size aluminum hydroxide.
[0022] As a preferred scheme, the mass ratio of the small particle size aluminum hydroxide, the medium particle size aluminum hydroxide and the large particle size aluminum hydroxide is (3~4):(5~6):1.
[0023] As a preferred scheme, the particle size of the small particle size aluminum hydroxide is 1~2μm; the particle size of the medium particle size aluminum hydroxide is 5~8μm; and the particle size of the large particle size aluminum hydroxide is 15~25μm.
[0024] The present application selects three different particle sizes of aluminum hydroxide for compounding, the large particle size aluminum hydroxide plays a role similar to a ball in the silicone potting adhesive, effectively reducing the friction and entanglement between particles and between particles and polymer molecular chains, and significantly reducing the viscosity of the composite material; the medium particle size aluminum hydroxide serves as the main flame retardant, and this particle size range can balance the flame retardant and basic performance, ensuring a large specific surface area so as to have sufficient reactivity, and avoiding the problems of serious agglomeration and high viscosity caused by too fine powder; the small particle size aluminum hydroxide can fill voids, improve the bulk density and enhance the flame retardant barrier effect.
[0025] As a preferred scheme, the flame retardant synergist is zinc borate and octaphenyl octasilsesquioxane. As a preferred scheme, the mass ratio of the zinc borate and the octaphenyl octasilsesquioxane is (1~2):1.
[0026] The present application uses zinc borate and octaphenyl octasilsesquioxane as the flame retardant synergist, the glassy coating generated by zinc borate at high temperature forms a composite barrier with the siloxane layer of octaphenyl octasilsesquioxane, the phenyl groups promote the formation of carbon layer through aromatization reaction, and the zinc ions generated by the decomposition of zinc borate can act as a carbon formation catalyst, thereby improving the carbon layer quality through carbon formation synergy, and effectively improving the flame retardant efficiency of the material.
[0027] As a preferred scheme, the viscosity of the vinyl silicone oil is 200~400mPa.s.
[0028] As a preferred scheme, the hydrogen content of the hydrogen-containing silicone oil is 0.5~1.2wt%.
[0029] As a preferred scheme, the platinum catalyst is Karstedt catalyst.
[0030] The second aspect of the present application provides a preparation method of the hydrogen-containing aluminum hydroxide-containing two-component silicone potting adhesive according to the first aspect, comprising the following steps: S1, 35~45 parts by weight of vinyl silicone oil, 50~60 parts of double-layer coated modified aluminum hydroxide, 4~6 parts of flame-retardant synergist, 0.03~0.09 parts of 1-ethynyl-1-cyclohexanol are added into a planetary mixer, and stirring is carried out under the conditions of a pressure of-0.07~-0.09 MPa and a temperature of 36~40 DEG C for 60~80 min to obtain an A component; S2, 20~30 parts of hydrogen-containing silicone oil, 0.08~0.16 parts of platinum catalyst are uniformly mixed to obtain a B component; S3, the A component and the B component are mixed and stirred for 40~60 min, and heated at 90~110 DEG C for 30~40 min to obtain a two-component silicone potting sealant containing aluminum hydroxide.
[0031] Compared with the prior art, the application has the following advantages and beneficial effects: 1. The application can control the material viscosity below 15000 cP, while ensuring good flame retardant performance and tensile strength, through the synergistic effect of aluminum hydroxide particle grading, the double-layer coated modification treatment of aminosilane and organic phosphite, and the flame-retardant synergist composed of zinc borate and octaphenyl octasilsesquioxane.
[0032] 2. The double-layer coated modified aluminum hydroxide of the application significantly improves the flame-retardant efficiency of the silicone potting sealant by the double-layer coating design of aminosilane and organic phosphite under the premise of reducing the addition amount of aluminum hydroxide, through phosphorus-silicon-nitrogen synergy (nitrogen element decomposes to generate inert gas to dilute oxygen, phosphorus element generates free radicals to inhibit combustion chain reaction, and silicon element forms a silicon skeleton to enhance the thermal stability of the carbon layer at high temperature); at the same time, the aminosilane layer of the double-layer coated modified aluminum hydroxide improves the interface bonding between the filler and the matrix, and the organic phosphite coating layer reduces the stress concentration and filler agglomeration, thereby increasing the tensile strength of the silicone potting sealant.
[0033] 3. The application selects three different particle sizes of aluminum hydroxide for compounding, the large particle size aluminum hydroxide plays a role similar to a ball bearing in the silicone potting sealant, effectively reducing the friction and entanglement between particles and between particles and polymer molecular chains, and significantly reducing the viscosity of the composite material; the medium particle size aluminum hydroxide serves as the main flame retardant, this particle size range can balance the flame retardant and basic performance, ensuring a large specific surface area to have sufficient reactivity, and avoiding the problem of serious agglomeration and high viscosity caused by too fine powder; the small particle size aluminum hydroxide can fill voids, improve packing density, and enhance the flame-retardant barrier effect.
[0034] 4. This invention uses zinc borate and octaphenyl octasesquioxane as flame retardant synergists. At high temperatures, the glassy coating generated by zinc borate forms a composite barrier with the silicon-oxygen layer of octaphenyl octasesquioxane. At the same time, the phenyl groups promote the formation of the char layer through aromatization reaction, while the zinc ions generated by the decomposition of zinc borate can act as a char-forming catalyst. Through synergistic char formation and improved char layer quality, the flame retardant efficiency of the material is effectively improved. Attached Figure Description
[0035] Figure 1 The image shows the X-ray diffraction patterns of multi-particle-size composite aluminum hydroxide and silanized aluminum hydroxide in Example 1.
[0036] Figure 2 The infrared spectra of multi-particle-size composite aluminum hydroxide and silanized aluminum hydroxide in Example 1 are shown. Detailed Implementation
[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0038] The sources of some components in the examples and comparative examples are as follows: Vinyl silicone oil, viscosity at 25℃ 200 mPa.s, vinyl content 2%, purchased from Zhejiang Hengyecheng Organosilicon Co., Ltd. Small-particle aluminum hydroxide, product number AH101.5, with a particle size of 1.5~1.7μm, moisture content <0.25%, and whiteness of 98, was purchased from Shandong Shibang Chemical Technology Co., Ltd. Medium-sized aluminum hydroxide, product number AH105, with a particle size of 5~6μm, moisture content <0.35%, and whiteness of 97, was purchased from Shandong Shibang Chemical Technology Co., Ltd. Large-particle aluminum hydroxide, product number AH1020, with a particle size of 18~22μm, moisture content <0.3%, whiteness >94, purchased from Shandong Shibang Chemical Technology Co., Ltd. Zinc phenylphosphine can be prepared according to the method in CN104262917A; Ferric ethylphenylphosphine can be prepared according to the method in CN104447859A; Zinc borate, CAS No. 10361-94-1, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Octaphenyl octasesquioxane, product number P102340, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. 1-ethynyl-1-cyclohexanol, CAS No. 78-27-3, purchased from Shanghai Macklin Biochemical Technology Co., Ltd.; Hydrogen-containing silicone oil, model RH-H503, hydrogen content 0.5wt%, purchased from Ningbo Runhe New Material Technology Co., Ltd.; Karstedt catalyst, part number M58817, purchased from Shanghai Maier Biochemical Technology Co., Ltd.
[0039] Example 1
[0040] The present embodiment provides a preparation method of a two-component silicone potting sealant containing aluminum hydroxide, comprising the following steps: S1, in parts by weight, 45 parts of vinyl silicone oil, 60 parts of double-layer coated modified aluminum hydroxide, 6 parts of flame-retardant synergist (4 parts of zinc borate and 2 parts of octaphenyl octasilsesquioxane), 0.09 parts of 1-ethynyl-1-cyclohexanol are added to a planetary mixer, and stirring is carried out under the conditions of a pressure of-0.09 MPa and a temperature of 40℃ for 60 min to obtain component A; S2, 30 parts of hydrogen-containing silicone oil and 0.16 parts of Karstedt catalyst are uniformly mixed to obtain component B; S3, the component A and the component B are mixed and stirred for 60 min, and heated at 110℃ for 30 min to obtain the two-component silicone potting sealant containing aluminum hydroxide.
[0041] Preparation of the double-layer coated modified aluminum hydroxide: in parts by weight, 90 parts of anhydrous ethanol and 10 parts of deionized water are uniformly mixed, then 4 parts of 3-aminopropyl triethoxysilane is uniformly stirred, and then 60 parts of multi-particle size compounded aluminum hydroxide (24 parts of small particle size aluminum hydroxide, 30 parts of medium particle size aluminum hydroxide and 6 parts of large particle size aluminum hydroxide) is added and reacted at 90℃ for 1h to obtain silanized aluminum hydroxide; 60 parts of silanized aluminum hydroxide and 3 parts of zinc phenylphosphinate are added to a planetary ball mill, and ball milling is carried out at a speed of 400 rpm for 20 min to obtain double-layer coated modified aluminum hydroxide.
[0042] Example 2
[0043] The present embodiment provides a preparation method of a two-component silicone potting sealant containing aluminum hydroxide, comprising the following steps: S1, in parts by weight, 35 parts of vinyl silicone oil, 50 parts of double-layer coated modified aluminum hydroxide, 4 parts of flame-retardant synergist (2 parts of zinc borate and 2 parts of octaphenyl octasilsesquioxane), 0.03 parts of 1-ethynyl-1-cyclohexanol are added to a planetary mixer, and stirring is carried out under the conditions of a pressure of-0.07 MPa and a temperature of 36℃ for 80 min to obtain component A; S2, 20 parts of hydrogen-containing silicone oil, 0.08 parts of Karstedt catalyst were uniformly mixed to obtain component B; S3, the component A and the component B were mixed and stirred for 40 min, and heated at 110°C for 30 min to obtain the two-component silicone potting sealant containing aluminum hydroxide.
[0044] The preparation of the double-layer coated modified aluminum hydroxide: 80 parts of anhydrous ethanol and 20 parts of deionized water were uniformly mixed, then 2 parts of 3-aminopropyl triethoxysilane was uniformly stirred, and then 50 parts of multi-particle size compounded aluminum hydroxide (20 parts of small particle size aluminum hydroxide, 25 parts of medium particle size aluminum hydroxide and 5 parts of large particle size aluminum hydroxide) was reacted at 70°C for 2h to obtain silanized aluminum hydroxide; 50 parts of silanized aluminum hydroxide and 1 part of iron ethyl phenyl phosphite were added to a planetary ball mill, and ball milled at a speed of 200 rpm for 40 min to obtain double-layer coated modified aluminum hydroxide.
[0045] Example 3
[0046] The present embodiment provides a preparation method of a two-component silicone potting sealant containing aluminum hydroxide, comprising the following steps: S1, 40 parts of vinyl silicone oil, 55 parts of double-layer coated modified aluminum hydroxide, 5 parts of flame-retardant synergist (3 parts of zinc borate and 2 parts of octaphenyl octasilsesquioxane), and 0.05 parts of 1-ethynyl-1-cyclohexanol were added to a planetary stirrer, and stirred at a pressure of -0.08 MPa and a temperature of 38°C for 70 min to obtain component A; S2, 25 parts of hydrogen-containing silicone oil, 0.12 parts of Karstedt catalyst were uniformly mixed to obtain component B; S3, the component A and the component B were mixed and stirred for 50 min, and heated at 100°C for 35 min to obtain the two-component silicone potting sealant containing aluminum hydroxide.
[0047] The preparation of the double-layer coated modified aluminum hydroxide: 85 parts of anhydrous ethanol and 15 parts of deionized water were uniformly mixed, then 3 parts of 3-aminopropyl triethoxysilane was uniformly stirred, and then 55 parts of multi-particle size compounded aluminum hydroxide (20 parts of small particle size aluminum hydroxide, 30 parts of medium particle size aluminum hydroxide and 5 parts of large particle size aluminum hydroxide) was reacted at 80°C for 1.5h to obtain silanized aluminum hydroxide; 55 parts of silanized aluminum hydroxide and 2 parts of zinc phenyl phosphite were added to a planetary ball mill, and ball milled at a speed of 300 rpm for 30 min to obtain double-layer coated modified aluminum hydroxide.
[0048] Comparative Example 1 The difference between the present comparative example and Example 1 is that multi-particle size compounded aluminum hydroxide is used instead of double-layer coated modified aluminum hydroxide.
[0049] Comparative Example 2 The difference between this comparative example and Example 1 is that the multi-particle size compounded aluminum hydroxide is replaced by double-layer coated modified aluminum hydroxide.
[0050] Comparative Example 3 The difference between this comparative example and Example 1 is that the multi-particle size compounded aluminum hydroxide is replaced by 30 parts of small particle size aluminum hydroxide and 30 parts of medium particle size aluminum hydroxide.
[0051] Comparative Example 4 The difference between this comparative example and Example 1 is that the multi-particle size compounded aluminum hydroxide is replaced by 48 parts of small particle size aluminum hydroxide and 12 parts of large particle size aluminum hydroxide.
[0052] Comparative Example 5 The difference between this comparative example and Example 1 is that the multi-particle size compounded aluminum hydroxide is replaced by 50 parts of medium particle size aluminum hydroxide and 10 parts of large particle size aluminum hydroxide.
[0053] Comparative Example 6 The difference between this comparative example and Example 1 is that the flame retardant synergist is all zinc borate.
[0054] Comparative Example 7 The difference between this comparative example and Example 1 is that the flame retardant synergist is all octaphenyl octasilsesquioxane.
[0055] Performance Test Viscosity test of component A: Test according to the requirements of GB / T 2794-2022 Adhesives-Determination of Viscosity.
[0056] UL94 grade test: Test according to the requirements of IEC 60695-11-10.
[0057] Oxygen index test: Test according to the requirements of ASTM D2863.
[0058] Thermal stability test: Test according to the requirements of ISO 11358 Plastics. Thermogravimetric analysis method (TG) of high polymers.
[0059] Tensile strength test: Test according to the requirements of GB / T 528-2009 Vulcanized rubber or thermoplastic rubber Determination of tensile stress-strain properties.
[0060] Table 1 Performance test results A group component viscosity (mPa.s) UL94 rating Oxygen index (%) 300°C thermal gravimetric analysis (wt%) Tensile strength (MPa) Example 1 12483 V-0 38.5 4.4 2.8 Example 2 14265 V-0 37.8 4.7 2.6 Example 3 13396 V-0 38.2 4.5 2.9 Comparative Example 1 15871 V-2 28.1 5.1 1.1 Comparative Example 2 15369 V-2 28.8 4.9 1.3 Comparative Example 3 30194 V-1 34.1 4.6 1.9 Comparative Example 4 16835 V-2 29.5 4.8 1.7 Comparative Example 5 12149 V-1 33.2 5.1 2.1 Comparative Example 6 14761 V-1 32.5 4.9 2.5 Comparative Example 7 14392 V-1 33.7 4.7 2.6 From the performance test results, it can be seen that the comprehensive performance of Examples 1-3 is the best, which is mainly because the synergistic effect of particle grading of aluminum hydroxide, combined with the double-layer coating modification treatment of aminosilane and phosphinate salt, and the flame-retardant synergist composed of zinc borate and octaphenyl octasilsesquioxane, can maintain low viscosity of the material while ensuring good flame-retardant performance and mechanical properties of the silicone pouring sealant.
[0061] Compared with Example 1, Comparative Example 1 uses multi-particle size compounded aluminum hydroxide instead of double-layer coated modified aluminum hydroxide, and lacks the effect of composite coating layer, so the flame retardancy is poor and the tensile strength is reduced; compared with Example 1, Comparative Example 2 uses multi-particle size compounded aluminum hydroxide instead of double-layer coated modified aluminum hydroxide, and lacks the effect of organic phosphite salt coating layer, so the flame retardancy is poor and the tensile strength is reduced; compared with Example 1, in Comparative Example 3, the multi-particle size compounded aluminum hydroxide is replaced by 30 parts of small particle size aluminum hydroxide and 30 parts of medium particle size aluminum hydroxide, which lacks the effect of large particle size aluminum hydroxide as a ball bearing, and the compounding effect is poor, so the viscosity of the material is significantly increased, the flame retardant performance is poor, and the tensile strength is reduced; compared with Example 1, in Comparative Example 4, the multi-particle size compounded aluminum hydroxide is replaced by 48 parts of small particle size aluminum hydroxide and 12 parts of large particle size aluminum hydroxide, which lacks medium particle size aluminum hydroxide as the main flame retardant and increases the amount of small particle size aluminum hydroxide, and the compounding effect is poor, so the viscosity of the material is increased, the flame retardant performance is poor, and the tensile strength is reduced; compared with Example 1, in Comparative Example 5, the multi-particle size compounded aluminum hydroxide is replaced by 50 parts of medium particle size aluminum hydroxide and 10 parts of large particle size aluminum hydroxide, which lacks small particle size aluminum hydroxide to enhance the flame retardant barrier effect, and the compounding effect is poor, so the flame retardant performance is poor and the tensile strength is reduced; compared with Example 1, in Comparative Example 6, the flame retardant synergist is zinc borate, and the synergist effect is poor, so the flame retardancy is poor; compared with Example 1, in Comparative Example 7, the flame retardant synergist is octaphenyl octasilsesquioxane, and the synergist effect is poor, so the flame retardancy is poor.
Claims
1. A two-component silicone potting sealant containing aluminum hydroxide, characterized in that, the two-component silicone potting sealant containing aluminum hydroxide is composed of component A and component B; the component A includes the following components by weight: 35-45 parts of vinyl silicone oil, 50-60 parts of double-coated modified aluminum hydroxide, 4-6 parts of flame-retardant synergist, and 0.03-0.09 parts of 1-ethynyl-1-cyclohexanol; the component B includes the following components by weight: 20-30 parts of hydrogen-containing silicone oil and 0.08-0.16 parts of platinum catalyst; the preparation method of the double-coated modified aluminum hydroxide comprises the following steps: firstly, coupling treatment of multi-particle size compounded aluminum hydroxide is performed using 3-aminopropyl triethoxysilane to obtain silanized aluminum hydroxide; and then, ball milling coating treatment of the silanized aluminum hydroxide is performed using organic phosphinic acid salt to obtain double-coated modified aluminum hydroxide. 2.The two-component silicone potting sealant containing aluminum hydroxide according to claim 1, characterized in that, the coupling treatment step includes the following steps: 80-90 parts of anhydrous ethanol and 10-20 parts of deionized water are uniformly mixed, then 2-4 parts of 3-aminopropyl triethoxysilane is added and stirred uniformly, and then 50-60 parts of multi-particle size compounded aluminum hydroxide is added and reacted at 70-90℃ for 1-2 hours to obtain silanized aluminum hydroxide. 3.The two-component silicone potting sealant containing aluminum hydroxide according to claim 1, characterized in that, the ball milling coating treatment step includes the following steps: 50-60 parts of silanized aluminum hydroxide and 1-3 parts of organic phosphinic acid salt are added to a planetary ball mill, and ball milling is performed at a speed of 200-400 rpm for 20-40 minutes to obtain double-coated modified aluminum hydroxide. 4.The two-component silicone potting sealant containing aluminum hydroxide according to claim 1, characterized in that, the organic phosphinic acid salt is zinc phenylphosphinate or iron ethylphenylphosphinate. 5.The two-component silicone potting sealant containing aluminum hydroxide according to claim 2, characterized in that, the multi-particle size compounded aluminum hydroxide includes small-particle-size aluminum hydroxide, medium-particle-size aluminum hydroxide and large-particle-size aluminum hydroxide; the mass ratio of the small-particle-size aluminum hydroxide, the medium-particle-size aluminum hydroxide and the large-particle-size aluminum hydroxide is (3-4):(5-6):
1. 6.The two-component silicone potting sealant containing aluminum hydroxide according to claim 5, characterized in that, the particle size of the small-particle-size aluminum hydroxide is 1-2 μm; the particle size of the medium-particle-size aluminum hydroxide is 5-8 μm; the particle size of the large-particle-size aluminum hydroxide is 15-25 μm. 7.The two-component silicone potting sealant containing aluminum hydroxide according to claim 1, characterized in that, the flame-retardant synergist is zinc borate and octaphenyl octasilsesquioxane; the mass ratio of the zinc borate and the octaphenyl octasilsesquioxane is (1-2):
1. 8.The two-component silicone potting sealant containing aluminum hydroxide according to claim 1, characterized in that, the viscosity of the vinyl silicone oil is 200-400 mPa·s. 9.The two-component silicone potting sealant containing aluminum hydroxide according to claim 1, characterized in that, The hydrogen content of the hydrogen-containing silicone oil is 0.5-1.2 wt%.
10. A preparation method of the two-component silicone potting sealant containing aluminum hydroxide according to any one of claims 1-9, comprising the following steps: S1. Adding 35-45 parts by weight of vinyl silicone oil, 50-60 parts by weight of double-coated modified aluminum hydroxide, 4-6 parts by weight of flame-retardant synergist, and 0.03-0.09 parts by weight of 1-ethynyl-1-cyclohexanol into a planetary mixer, and stirring under the conditions of a pressure of-0.07 to-0.09 MPa and a temperature of 36-40°C for 60-80 min to obtain component A; S2. Mixing 20-30 parts by weight of hydrogen-containing silicone oil and 0.08-0.16 parts by weight of platinum catalyst uniformly to obtain component B; S3. Mixing and stirring the component A and the component B for 40-60 min, and heating under the condition of a temperature of 90-110°C for 30-40 min to obtain the two-component silicone potting sealant containing aluminum hydroxide.
Citation Information
Patent Citations
Preparation method of high-molecular polylactic acid (PLA) three-dimensional composite material capable of being crystallized rapidly
CN104262917A
Synthesis process of phosphinate containing alkylaryl
CN104447859A